Peran Manajemen Sumber Daya Manusia dalam Mewujudkan Lingkungan Kerja Islami - Pitriani; Zainal Berlian; Baharudin (STKIP Subang, 2026)
In this study, we look at how human resource management (HRM) plays a role in creating and maintaining an Islamic work environment within contemporary organizations. An Islamic work environment is characterized by values like amanah (trustworthiness), ihsan (excellence), adl (justice), integrity, mutual respect, and accountability, all of which are based on Islamic ethical principles. The study highlights how HRM works, including recruitment and selection, training and development, performance appraisal, compensation management, and employee relations, and how they serve as strategic tools for embedding these values into the culture of the company. Organisasi dapat menarik orang-orang dengan keyakinan pribadi yang sesuai dengan nilai-nilai Islamic. Program pelatihan terus menerus meningkatkan kesadaran spiritual, keterampilan profesional, dan pilihan moral. Dengan partisipasi pemimpin dan komunikasi yang efektif, brotherhood (ukhuwah) dan tanggung jawab kolektif dipromosikan. Di sisi lain, sistem kompensasi yang adil dan evaluasi kinerja yang adil mencerminkan prinsip keadilan. Selain itu, HRM policies yang mendukung keseimbangan antara kerja dan kehidupan pribadi, kegiatan spiritual, dan perilaku moral membantu mewujudkan lingkungan kerja yang sehat dan harmonis. The article claims that adding Islamic principles to HRM practices increases employee commitment and job satisfaction. It also says that it improves organizational performance and sustainability in the long term. Dengan meletakkan HRM sebagai moral dan strategis driver, organisasi dapat membuat a productive work environment yang balances material achievement with spiritual growth. Ultimately, Islamic-based HRM encourages ethical behavior, strengthens organizational identity, and supports the development of high-quality human resources grounded in faith and professionalism.